Evaluation of the Effect of Methotrexate on Psoriasis Based on Specialized Pharmaceutical Education - Wang, Lan; Shu, Dan; Mao, Chien Tai; Zhao, Yi; AI, Chao (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Methotrexate (MTX) is still the gold standard therapy for moderate to severe psoriasis. There is a marked interpersonal variation in the therapeutic response and toxicity profile of MTX which brings difficulty for clinical application. Objectives: To establish the specialized pharmaceutical education (SPE) mode for psoriasis administrated with MTX and assess the therapeutic effect between cases received SPE and usual health care in the real-world. Materials and Methods: In this retrospective cohort study, patients of usual health care received prescription as proof of properly taking medicine and being required return to the hospital every 4 weeks. Patients of SPE intervention were referred to the pharmaceutical clinic every 4 weeks. Body surface area(BSA), psoriasis area severity index (PASI) of 0, 4, 8, 12 week, PASI 75 of 12 week and times of selfadjusting dosage were observational noted and analyzed. Results: Records of 12 cases of usual care and 16 cases of SPE received MTX for psoriasis were reviewed. The decline range of BSA of SPE was higher than that of usual care at 4 week, and the difference was statistically significant (p=0.043).The decline range of PASI of SPE was higher than that of usual care at 8 week and 12 week with statistically significant difference separately (p=0.048; p=0.029).Times of self-adjusting dosage was zero of SPE and was statistically significant different compared to that of usual care (p=0.026). Conclusion: Statistical significant faster improvement on efficacy with no significant difference of safety in the SPE than usual care came to the conclusion. The SPE conducted by the pharmacists appears suitable for the real world implementation.
Keywords: Methotrexate; Psoriasis vulgaris; Pharmaceutical education; Effect evaluation; Real world implementation